Health benefits of xylitol consumption - a literature review - Martyna Brzoza; Julia Stawińska-Dudek; Piotr Mikołajczyk; Barbara Buras; Milena Orzeł; Bartłomiej Orzeł; Aleksandra Bielecka; Bartosz Dubniański; Kornelia Stawińska (Journal of Education, Health and Sport)
Introduction and purpose: